2022
DOI: 10.1136/bmjopen-2021-058380
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing decisions about whether to participate in health research by people of diverse ethnic and cultural backgrounds: a realist review

Abstract: ObjectiveTo develop and refine a programme theory that explains factors that influence decisions to take part in health research by people of diverse ethnic and cultural backgrounds.DesignRealist review following a sequence of five steps: (a) scoping search and identification of programme theory; (b) evidence searching; (c) critical appraisal and data extraction; (d) organisation of evidence and (e) refinement of programme theory.Eligibility criteriaDocuments (including peer-reviewed articles, grey literature,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…Nonetheless, evidence from a review of UK non-cancer studies has shown how the complicated consent process and lengthy and complex patient information materials, aimed at safeguarding patients, can act as a deterrent to participation. 38 In addition, negative assumptions and lack of cultural understanding among recruiters may lead to a reluctance to approach patients from minority groups. An additional factor underlying lack of diversity may be the priorities of hospitals themselves.…”
Section: Reviewmentioning
confidence: 99%
“…Nonetheless, evidence from a review of UK non-cancer studies has shown how the complicated consent process and lengthy and complex patient information materials, aimed at safeguarding patients, can act as a deterrent to participation. 38 In addition, negative assumptions and lack of cultural understanding among recruiters may lead to a reluctance to approach patients from minority groups. An additional factor underlying lack of diversity may be the priorities of hospitals themselves.…”
Section: Reviewmentioning
confidence: 99%